La coopération internationaledans la recherche-action en éducation. Un autre moyen de concevoir et de mettre en œuvre la formation des enseignants - Jeanne Mallet; Florence Saint-Luc (Éducation et Socialisation)
The teacher training is determining in the prevention of school violences. An action-research started in July 08, within the Modern School movements, in the form of an international cooperation for the training: participating observations were carried out in classes and during trainings in Finland, Belgium, Germany, Spain and finally in Portugal, where a form of research-action for the training has been developed since 1974, offering a setting proof for the concept of isomorphism Education/Training/Research. The visits and the animation of interventions allowed a posture of upractitioner-researcherv in the training area, in the form of a co-operative self-tuition, integrated in a training to and by the research-action, for teachers/trainers, inside an international co-operative network.